Teaching and learning process for mathematization activities: The case of solving maximum and minimum problems - Jupri, Al; Usdiyana, Dian; Sispiyati, Ririn (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2021)
One of the topics within the course of Essential Concepts in School Mathematics (ECSM) for prospective mathematics teachers concerns maximum and minimum problems. This type of problems requires mathematization, i.e., the activity of transforming a problem into a symbolic mathematics problem and of reorganizing within the mathematical system, in the solution process. This research aims to investigate the implementation of the learning and teaching process of the ECSM course that strengthen prospective mathematics teachers’ conceptual understanding and problem solving abilities through mathematization activities. To reach this aim, this qualitative study was conducted through an observation of the learning and teaching process, including the formative written assessment, for the case of maximum and minimum problems, involving 19 students of mathematics education program. The results of this study revealed that the learning and teaching process is implemented by emphasizing the use of a deductive approach. The written assessment showed students’ strategies and difficulties in dealing with maximum and minimum problems. Main difficulties included constructing visual representations and mathematical models in the mathematization processes. It can be concluded that the learning and teaching processes of the ECSM course need to be improved so as to develop better conceptual understanding and problem solving abilities through mathematization activities.